2011
DOI: 10.1080/00380768.2010.548310
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide and methane emissions from grassland treated with bark- or sawdust-containing manure at different rates

Abstract: On the main Japanese island of Honshu, bark or sawdust is often added to cattle excreta as part of the composting process. Dairy farmers sometimes need to dispose of manure that is excess to their requirements by spreading it on their grasslands. We assessed the effect of application of bark-or sawdust-containing manure at different rates on annual nitrous oxide (N 2 O) and methane (CH 4 ) emissions from a grassland soil. Nitrous oxide and CH 4 fluxes from an orchardgrass (Dactylis glomerata L.) grassland that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The fundamental reason for using various additives in composting processes is to provide the best-growing environment for microbial growth and achieve rapid composting, thus reducing the harmful gas emissions under controlled conditions. For example, sawdust is an additive that reduces methane emissions to a certain extent [4]. However, the quality of the fertilizer ultimately depends on the microbial composition of the compost, and only a clear understanding of the succession pattern of the microbial communities throughout the composting stages will enable us to fully control this process.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental reason for using various additives in composting processes is to provide the best-growing environment for microbial growth and achieve rapid composting, thus reducing the harmful gas emissions under controlled conditions. For example, sawdust is an additive that reduces methane emissions to a certain extent [4]. However, the quality of the fertilizer ultimately depends on the microbial composition of the compost, and only a clear understanding of the succession pattern of the microbial communities throughout the composting stages will enable us to fully control this process.…”
Section: Introductionmentioning
confidence: 99%
“…Akiyama and Tsuruta (2003) reported that N 2 O emissions were 0.08% and 0.05% of applied N for dried cattle excreta (C/N rate of 24.3) and for cattle manure (C/N rate of 15.9), respectively. Mori and Hojito (2011) reported that manure-induced EF of bark-or sawdust-containing manures was 0.068% in orchard grassland in Tochigi. These values are relatively smaller than manure-induced EF in our study.…”
Section: N 2 O Emission Factormentioning
confidence: 99%
“…Therefore, annual N 2 O emissions have spatial and/or inter-annual variation due to the variations in soil and climate (Lu et al 2006;Gu et al 2007;Gu et al 2009;Mori and Hojito 2012). Furthermore, the application of chemical N fertilizer and livestock manure could augment N 2 O emissions, and N 2 O emissions can be affected by fertilizer type (Bouwman et al 2002a;Akiyama and Tsuruta 2003;Akiyama et al 2006;Mori and Hojito 2011). Manure with a high and easily mineralizable organic C content stimulates microbial activity and thus N 2 O emissions (Drury et al 1991;Chadwick et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The N 2 O EF of synthetic fertilizer (0.1%-5.7%) increases with increasing annual mean air temperature (5.2-15.8°C) and precipitation (1160-2595 mm year −1 ), but the N 2 O EF of FYM (−3.2% to +1.3%) has shown no clear relationships (Shimizu et al 2013). The smaller N 2 O EF for FYM is due mainly to less inorganic N in FYM as compared with synthetic fertilizer (Mori and Hojito 2011). The background N 2 O emissions (0.2-4.2 kg N ha −1 year −1 ) also increase with increasing temperature and precipitation.…”
Section: N 2 O Emissions From Grasslands In Japanmentioning
confidence: 95%